Геомеханическое состояние угольных пластов при подходе очистных работ к разрывным нарушениям сложной морфологии - Скипочка, С.И.; Пилипенко, Ю.И. (Геотехническая механика, 2009)
Представлено аналітичний опис напруженого вугільного пласта в зоні малоамплитудных тектонічних порушень шляхом суперпозиції двох рішень: про опорний тиск і про еліптичне включення пружної області. При зміні величин осей еліпса й кута нахилу отримане рішення для широкого класу розривних структур. An analitical discription of a peak-stressed coal mass in a zone of small amplitude tectonic disturbances is given in this article when this is done bu means of a superposition of two solutions: a solution about the rock pressure near the face and a solution about an elliptic inclusion in an elastic zone. By means of changing of the value of ellips axes and the angle of the inclination a solutionhas bee received for a wide classof failured structures.